IMPLIKASI MANAJEMEN TALENTA PADA KEPUASAN BEKERJA PADA CV PUTRA MAS PRATAMA MEDAN - VISILLIA EDELWISA; KEVIN AZIS (LP2MTBM MAKARIOZ, 2018)
CV Putra Mas Pratama is a moving company in the field of preparation of building construction materials having talent management in the HR and Humas departments, where the process of HR capability selection, placement (organization), and the process of development and training of prospective employees to be employed still raises problems, where HR planning processes, organization, and unmaximized supervision are carried out on HR capabilities and expertise, where there is still a SDM that is scored from the process of development of this talent management has not been up to expectations, some even do not fit its field in the organizational structure of the company, so that the process of developing the talent and capabilities of the HR cannot be done to the maximum, so it is obtained that HR that does not have the strong will to work, as well as having the motivation in completing the work according to the established time, thus leading to a decrease in motivation and work morale, which ultimately lowers the job satisfaction of employees, thus focusing on the decline in HR performance as well as the CV of Putra Mas Pratama. This study aimed to find out whether talent management processes such as HR ability selection, placement (organization), and HR development and training processes have a significant impact on the job satisfaction of CV employees of Putra Mas Pratama. The data analysis on this study used validity and reliability tests, double linear regression analysis and hypothetical tests, where the population and samples in this study were employees of the CV of Putra Mas Pratama Medan of 51 people. The results of this study state that definitively and partially the process of talent management consisting of the process of selection of HR capabilities, the process of placement of HR, and the process of development and training of HR has a significant impact on the job satisfaction of CV employees of Putra Mas Pratama Medan.